(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Bogomaz-Nazarov S. Interdisciplinary communication as a condition for improving the quality of didactic training of future teachers. In this article the analysis of intersubject connections is examined in methodical literature as important component at an increase efficiency of teaching.